2021
DOI: 10.1186/s13063-021-05579-w
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the curative effect of Guizhi-Shaoyao-Zhimu decoction combined with methotrexate in the treatment of early rheumatoid arthritis based on ultrasonic evaluation: study protocol of a randomized, double-blind, controlled clinical trial

Abstract: Background Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease with the primary clinical symptoms of joint swelling and pain. Early detection of erosion and synovial inflammation at an active stage resulting from RA can prevent damage to the joints and activity restriction. However, there are still many patients who do not respond to these treatments; the development of newer, safer drugs is urgently needed. Compared to Western medicine, Guizhi-Shaoyao-Zhimu decoction has equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the infection and tumor risks associated with their prolonged utilization require further assessment ( Burmester et al, 2015 ; Tanaka, 2023 ). In recent years, several randomized controlled trials (RCTs) have indicated that combining traditional Chinese herbal medicine with Western medicine is superior to Western medicine alone, providing both better outcomes and fewer adverse reactions ( Gong et al, 2021 ; Shen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the infection and tumor risks associated with their prolonged utilization require further assessment ( Burmester et al, 2015 ; Tanaka, 2023 ). In recent years, several randomized controlled trials (RCTs) have indicated that combining traditional Chinese herbal medicine with Western medicine is superior to Western medicine alone, providing both better outcomes and fewer adverse reactions ( Gong et al, 2021 ; Shen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a single herb, the compounded medication prescription like "Guizhi-Shaoyao-Zhimu decoction" can also receive positive curative effects. Recent clinical research has shown that the clinical cure rate of "Guizhi-Shaoyao-Zhimu decoction" for RA patients is around 90%, which is higher than that of indomethacin, tripterygium glycosides, and prednisonec (41). It infers that TCM is a proper alternative option in the treatment of rheumatoid arthritis pain.…”
Section: Introductionmentioning
confidence: 99%